The Role of The National Land Agency in Monitoring The Issuing Land Deed by The Temporary Land Deed Officer in Indramayu Regency - Sabrina Widya Astuti (Authentica, 2019)
This study aims to analyze how the role of the National Land Agency in terms of supervision of the making of a land deed by the Acting Land Actor in the District of Indramayu. based on research that has been carried out the role of supervision carried out by the National Land Agency in Indramayu Regency contained in the regulation of the Minister of Agrarian Affairs and Spatial Planning No. 2 of 2018 concerning Supervision and Development of Land Deed Making Officials. Research shows that supervision of the Temporary Land Deed Making Officials in Indramayu Regency has not been carried out by the National Land Agency. Supervision based on Permen ATR Number 2 of 2018 namely preventive and repressive supervision. Preventive supervision is to supervise the implementation of the PPAT position while repressive supervision is carried out by enforcing the rule of law in accordance with statutory provisions in the PPAT field. Keywords: National Land Agency, supervision, PPAT